2023
DOI: 10.1177/09763996221138465
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Relationship Between Financial Development, Economic Growth, Foreign Direct Investment and Trade Openness: Evidence from South Asian Countries

Abstract: This study examines the nature of the association among financial development, economic growth, foreign direct investment and trade openness in four South Asian countries from the period 1990–2019. The study employed Granger Causality test in Vector Error Correction Model (VECM) framework to find out the dynamic relationship among the variables. Further, variance decomposition analysis (VDA) and impulse response function (IRF) is also applied to determine the relationships among the variables beyond the sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The study found no long-term relationship among all three variables, but FDI causes economic growth, and economic growth causes FDI, confirming bidirectional causality. Mustafa (2023) examined the relationship between financial development, economic growth, foreign direct investment, and trade openness in four South Asian countries from 1990 to 2019 using the Granger Causality test in the Vector Error Correction Model (VECM) framework. The results suggest that all four countries should adopt policies to promote further trade liberalization, financial sector development, and fast-track reforms to improve the investment climate and attract investments to attain high economic growth in the long run.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study found no long-term relationship among all three variables, but FDI causes economic growth, and economic growth causes FDI, confirming bidirectional causality. Mustafa (2023) examined the relationship between financial development, economic growth, foreign direct investment, and trade openness in four South Asian countries from 1990 to 2019 using the Granger Causality test in the Vector Error Correction Model (VECM) framework. The results suggest that all four countries should adopt policies to promote further trade liberalization, financial sector development, and fast-track reforms to improve the investment climate and attract investments to attain high economic growth in the long run.…”
Section: Literature Reviewmentioning
confidence: 99%